" The relationship between family support and children's ability to adapt to academic pressures "Case study: Sociology Department students at Tishreen University (Damascus University Journal of arts and humanities sciences, 2026)
The descriptive analytical approach, the social survey method with a sample, and the scale (family support and study pressures) was used as a research tool, which was prepared by the researcher, as its phrases amounted to (40) phrases in order to determine the nature of family support provided to children and its relationship to their adaptation to study pressures and dealing with them. A regular random sample of students from the Department of Sociology at Tishreen University was drawn, numbering (250) male and female students. After collecting the data, it was unloaded and analyzed using the SPSS program, and a set of results were reached, the most important of which were:the existence of a strong negative relationship between family support and study pressures. The results showed that material support tops the forms of support, while cognitive and psychological support needs further development to enhance positive interaction between the family and the student. The study also showed that the academic pressures faced by students vary between anxiety related to tests, time management, and the difficulty of the study materials. It also showed some differences in the family support that children receive according to some variables such as: family income in favor of those whose family income is (between 300 thousand and one million per month), and according to the variable of the father's education level in favor of higher education, as the higher the father's education level, the greater the support, as well as for the mother's education level, where the differences were in favor of university mothers. It also showed that there were no differences according to the variable of the number of family members. At the end of the research, a set of proposals were presented that contribute to strengthening the role of the family in order to provide support to children to improve their ability to face academic challenges.
Keywords: Family; Family Support; Adaptation; Study Pressures; University Youth